Electrochemical Behavior of Mild Steel in Dimethyl Sulfoxide Containing Hydrochloric Acid - Rastogi,R.B. (2010)
The corrosion behavior of mild steel in dimethyl sulfoxide containing various concentrations, i.e., 0.001, 0.005, 0.010, 0.015 and 0.020 M of hydrochloric acid has been studied in presence of 0.1 M tetra ethyl ammonium chloride as supporting electrolyte by applying electrochemical techniques. The results of these experiments have been supplemented by surface analysis of the samples exposed to corrosive solution under different experimental conditions. The electrochemical investigation was done potentiostatically by varying the concentration of HCl in DMSO and the experimental temperature as well.